Antibody and B cell responses to an investigational adjuvanted RSV vaccine for older adults. Issue 10 (3rd October 2019) - Weinberg, Adriana; Lambert, Stacie L; Canniff, Jennifer; Yu, Li; Lang, Nancy; Esser, Mark T; Falloon, Judith; Levin, Myron J
ABSTRACT: Background : Infections with respiratory syncytial virus (RSV) cause significant morbidity and hospitalization in older adults. We studied the humoral, mucosal and B cell responses of an investigational adjuvanted RSV sF vaccine, MEDI7510, in older adults. Methods : In a substudy of a randomized (1:1), double-blind, placebo-controlled study of MEDI7510 in adults ≥60 years of age, we collected blood and nasal secretions at days 0, 8, 29, 91 and 180 post-vaccination to measure F-specific IgG and IgA antibodies by ELISA, and plasmablasts and memory B cells by IgA/IgG dual-color fluorospot. Results : The 27 vaccine- and 18 placebo-recipients had a mean age of 73 years and included 24 women. Among vaccinees, 93% had significant increases in F-specific plasma IgG 85% had increased plasma IgA; 74% had increased nasal IgG and 26% nasal IgA; 93% had IgG and 89% IgA plasmablasts on Day 8 post-immunization; and 82% had IgG and 7.4% IgA memory B cell responses to the vaccine. Vaccinees <70 years of age and women had the highest responses to the vaccine. Conclusions : This adjuvanted vaccine generated robust humoral immune responses in older adults, including RSV F-specific systemic and mucosal antibodies and memory B cells. Nevertheless, age ≥70 years was associated with decreased immunogenicity of the adjuvanted vaccine.